Do photobionts influence the ecology of lichens? A case study of environmental preferences in symbiotic green alga Asterochloris (Trebouxiophyceae) - Peksa, Ondřej; Skaloud, Pavel (Molecular ecology, 2011)
The distribution patterns of symbiotic algae are thought to be conferred mainly by their hosts, however, they may originate in algal environmental requirements as well. In lichens, predominantly terrestrial associations of fungi with algae or cyanobacteria, the ecological preferences of photobionts have not been directly studied so far. Here, we examine the putative environmental requirements in lichenized alga Asterochloris, and search for the existence of ecological guilds in Asterochloris-associating lichens. Therefore, the presence of phylogenetic signal in several environmental traits was tested. Phylogenetic analysis based on the concatenated set of internal transcribed spacer rDNA and actin type I intron sequences from photobionts associated with lichens of the genera Lepraria and Stereocaulon (Stereocaulaceae, Ascomycota) revealed 13 moderately to well-resolved clades. Photobionts from particular algal clades were found to be associated with taxonomically different, but ecologically similar lichens. The rain and sun exposure were the most significant environmental factor, clearly distinguishing the Asterochloris lineages. The photobionts from ombrophobic and ombrophilic lichens were clustered in completely distinct clades. Moreover, two photobiont taxa were obviously differentiated based on their substrate and climatic preferences. Our study, thus reveals that the photobiont, generally the subsidiary member of the symbiotic lichen association, could exhibit clear preferences for environmental factors. These algal preferences may limit the ecological niches available to lichens and lead to the existence of specific lichen guilds.
Keywords: DNA primery; Base Sequence; California; Evropa; DNA, Ribosomal Spacer; Ecosystem; Environment; lišejníky; sekvenční seřazení; Chlorophyta; aktiny; fylogeneze; Actins; životní prostředí; Kalifornie; ekosystém; Sequence Analysis, DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Molecular Sequence Data; Europe; Lichens; Sequence Alignment; Phylogeny; mezerníky ribozomální DNA; sekvence nukleotidů; DNA Primers